Navigating uncertainty: a valuable cost‐effectiveness analysis in the rapidly changing field of metastatic melanoma treatment. (December 2015) - Curl, P.K.
Abstract : Linked Article: Matter‐Walstra, et al . Br J Dermatol 2015;173 :1462–70 .